1998
DOI: 10.1073/pnas.95.22.12977
|View full text |Cite
|
Sign up to set email alerts
|

Increase of intracellular Ca 2+ and relocation of E-cadherin during experimental decompaction of mouse embryos

Abstract: To determine the role of intracellular Ca 2؉ in compaction, the first morphogenetic event in embryogenesis, we analyzed preimplantation mouse embryos under several decompacting conditions, including depletion of extracellular Ca 2؉ , blocking of Ca 2؉ channels, and inhibition of microfilaments, calmodulin, and intracellular Ca 2؉ release. Those treatments induced decompaction of mouse morulae and simultaneously induced changes in cytosolic free Ca 2؉ concentration and deregionalization of E-cadherin and fodrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 82 publications
2
36
0
1
Order By: Relevance
“…6B), suggest that anandamide primarily influences N-type Ca 2ϩ channels in the blastocyst trophectoderm. This is consistent with previous observations that Ca 2ϩ signaling is crucial for blastocyst formation (28) and that N-type Ca 2ϩ channels are functionally coupled to the stimulating effects of heparin-binding EGF-like growth factor (HB-EGF) in blastocyst development and outgrowth (22).…”
Section: Anandamide At High Concentration Inhibits Depolarization-indsupporting
confidence: 81%
“…6B), suggest that anandamide primarily influences N-type Ca 2ϩ channels in the blastocyst trophectoderm. This is consistent with previous observations that Ca 2ϩ signaling is crucial for blastocyst formation (28) and that N-type Ca 2ϩ channels are functionally coupled to the stimulating effects of heparin-binding EGF-like growth factor (HB-EGF) in blastocyst development and outgrowth (22).…”
Section: Anandamide At High Concentration Inhibits Depolarization-indsupporting
confidence: 81%
“…During cleavage-stage biopsies, Ca +2 /Mg + 2 -free medium is used in order to loosen cell-to-cell adhesion and facilitate selected blastomere removal. Several murine studies showed that Ca +2 depletion caused remodeling of the cellular cytoskeleton, inevitably affecting compaction [35][36][37][38]. Furthermore, artificial breaching of the zona pellucida by means of the laser system to enable blastomere biopsy may increase local temperature for a few milliseconds and potentially impact subsequent development [39], although Taylor et al had shown that laser pulse does not influence embryo development when the size of the hole is controlled [40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…E-cadherin mediates compaction of the individual blastomeres in the 8-cell stage embryo, and this adhesion triggers the development of the trophectoderm and other epithelial cell layers at later developmental stages (Gumbiner, 1996). In embryos, mutation of E-cadherin, perturbation of the function of molecules interacting with E-cadherin, or disturbance of the compaction process, all lead to the relocation of E-cadherin, and of the molecules interacting with it (Clayton et al, 1999;Ohsugi et al, 1997;Pey et al, 1998).…”
Section: Introductionmentioning
confidence: 99%